2003
DOI: 10.4049/jimmunol.170.10.4914
|View full text |Cite
|
Sign up to set email alerts
|

Two Regions of Down-Regulation in the IgE-Mediated Signaling Pathway in Human Basophils

Abstract: Previous studies demonstrated that after stimulation of human basophils with a polyclonal anti-IgE Ab, early signaling elements showed sustained phosphorylation, whereas later elements were transient, suggesting that a region of down-regulation involved inhibition of phosphatidylinositol (PI) 3 kinase or its products. However, the current studies show that under some conditions, syk phosphorylation is transient. Generally, stimulation with a variety of Ags makes this early form of down-regulation more apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 39 publications
6
32
1
Order By: Relevance
“…From these data, different mechanisms that might lead to loss of patient's responsiveness during semirush immunotherapy have been postulated (36)(37)(38)(39)(40). As in vitro stimulation of basophils closely resembles the in vivo pathway finally leading to symptoms, we speculated that suppression of venom-induced CD63 expression during treatment might be an in vitro correlate of clinical tolerance and be useful to monitor successful VIT.…”
Section: Discussionmentioning
confidence: 99%
“…From these data, different mechanisms that might lead to loss of patient's responsiveness during semirush immunotherapy have been postulated (36)(37)(38)(39)(40). As in vitro stimulation of basophils closely resembles the in vivo pathway finally leading to symptoms, we speculated that suppression of venom-induced CD63 expression during treatment might be an in vitro correlate of clinical tolerance and be useful to monitor successful VIT.…”
Section: Discussionmentioning
confidence: 99%
“…This acute mechanism for FcεRI downregulation does not appear to involve FcεRI/antigen internalization or Syk loss. Recent studies by MacGlashan [25 ]demonstrated that antigen stimulation of basophils induces downregulation operating before or at the level of Syk phosphorylation. In these experiments basophils were challenged with antigen for less than 2 h before challenge with anti-IgE.…”
Section: Discussionmentioning
confidence: 99%
“…In the relatively short time frame of typical experiments, down-regulation or desensitization is not the loss of cell surface receptors but instead appears to be the result of changes in the signaling apparatus (1). We have identified two regions of down-regulation occurring during IgE-mediated secretion (2). The earliest process precedes the activation of syk kinase but a second process, occurring at a point just distal to the activation of PI3K, occurs simultaneously with the receptor-proximal process (3).…”
Section: And Natalia Vilariñ Omentioning
confidence: 99%
“…In previous studies, we did not find any evidence of the interaction of the Fc portion of our goat anti-IgE Ab with Fc␥RIIb known to be present on basophils (2). However, activation of SHIP is expected by co-cross-linking of Fc␥RIIb with Fc RI (25,32,33), so we re-examined stimulation with anti-IgE Ab (0.2 g/ml) in the presence of high concentrations of nonspecific human IgG (previously shown to modify association of mIgG with Fc␥RIIb on basophils (2)).…”
Section: Characterization Of Ship Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation